From the silenced voices in the Surandino, new lines of emancipatory thought resurface (Revista revoluciones, 2019)
We are attending more complex times of crisis, because today we are confined to the virus or under its name we are locked, invisibilized, threatened and susceptible to contagion. The objective is to contextualize the lines of thought and action of its promoters. Various publications and productions have been tracked in the methodology in this perspective. The results show us that Revolución is a publication that arises and is born from those silenced and relegated voices, a collective that decides to accept lines and actions of emancipatory thought. It will give much to talk, debate, especially face and embody on the ways of doing political, humanities and social science. It is complex to start, open the veils of exclusion and enter the arena of debate, but within the framework of respect and humility without violence or passion. A true weapon of the revolution in the current times is education, and this implies being truly revolutionary in our ways of thinking, doing, knowing, acting, loving and acting for human dignity, in this case for the dignity of our peoples of all bloods.
Keywords: Criticism; emancipation; struggle; thought; other voices